Dr David Malan DM, FRCPsych (1922–2020): A breath of fresh air for psychoanalysis and mental health. (June 2023) - Ezquerro, Arturo; Allen, Daniel
This hybrid piece of work aims to pay tribute to David Malan (21 March 1922–14 October 2020) who has been one of the great influences on open-minded psychoanalysis and psychodynamic mental health. Inspired by the work and ideas of John Bowlby, Michael Bálint and Habib Davanloo, over five decades, Dr Malan committed himself to finding effective treatments that would help the largest number of patients in the shortest possible time, and pioneered research into brief dynamic psychotherapy as well as into group psychotherapy. He came to the conclusion that the type of therapy matters far less than the relationship the patient has with the therapist or therapy group, since patients can explore more confidently and make progress more significantly when they perceived the therapist or therapy group as a secure base, a key tenet of attachment theory. More specifically, he pursued a new tradition of short-term psychotherapy that built a bridge between psychoanalytic and more active cognitive-behavioural approaches, and managed to live up to the high ambition for integration of science and meaning in psychiatry, psychotherapy (including group psychotherapy) and psychoanalysis.